Anti-CD38 monoclonal antibodies in multiple myeloma and beyond: immunotherapeutic mechanisms, evidence maturity, and clinical positioning - Liming Yu; Changnian Li; Dadong Guo; Siyuan Cui (Frontiers in Immunology, 2026)
Anti-CD38 monoclonal antibodies have become a central immunotherapeutic platform in multiple myeloma, where they have reshaped treatment across relapsed or refractory disease, frontline therapy, maintenance intensification, and minimal residual disease-oriented management. Their success in multiple myeloma has also stimulated broader development in immunoglobulin light-chain amyloidosis, selected hematologic malignancies, and humoral immune-mediated disorders. CD38 functions both as a surface target and as an ectoenzyme involved in nicotinamide adenine dinucleotide metabolism, calcium signaling, immune-cell regulation, and microenvironmental remodeling, providing a mechanistic basis for antibody-mediated cytotoxicity, immune modulation, and broader humoral immune intervention. This Review critically evaluates CD38 biology, Fc-mediated immune-effector mechanisms, immune remodeling, clinical evidence, resistance, safety, laboratory interferences, biomarker evidence, and clinical positioning of anti-CD38 antibodies, with multiple myeloma as the central reference disease. In immunoglobulin light-chain amyloidosis, daratumumab-based therapy has moved beyond myeloma-derived extrapolation and established a disease-specific framework integrating hematologic response, organ response, and survival outcomes. Beyond multiple myeloma, anti-CD38-based strategies have been investigated in light-chain amyloidosis, selected hematologic malignancies, autoimmune cytopenias, transplant-related alloimmunity, and other antibody-driven diseases. However, the strength of evidence differs substantially across these settings, and CD38 expression alone does not establish clinical benefit. Outside established plasma cell disorders, further development should therefore rely on disease-specific prospective evidence and careful assessment of safety.